Neutron stars for training high-school teachers. Issue 1 (1st June 2022) - Giliberti, E; Perotti, L; Giliberti, M
Abstract: In this period of COVID-19 emergency, online inquiry-based educational paths are of crucial importance for school. Here, we present a didactic path for training high-school teachers to be developed online, using as a starting point the physics of neutron stars. Our aim is to train teachers in performing at distance inquiry activities based on real experimental data and in acquiring the skills to use such activities in classwork. The path is scheduled to be tested for the first time in Spring 2021.